Rancang Bangun Remote-Control Monitoring System (RCMS) pada peralatan Navigasi Udara NDB di Makassar Air Traffic Service Center berbasis Internet of Thing (IoT) - Purbo Wartoyo, Bayu; Kuswara, Gatot; Roby Syaritno, M.; Sinaga, Ucok (Politeknik Penerbangan Makassar, 2020)
â€œDesign of Remote-Control Monitoring System (RCMS) on NDB Air Navigation equipment in Makassar Branch Cluster (MATSC) based on Internet of Thing (IoT)â€. The benefits of RCMS include; Can assist maintenance technicians in carrying out maintenance tasks at a certain level, as a form of synergy and collaboration between the aviation industry and vocational education, with this RCMS, better data will be obtained for further research. The objectives of this design are; Designing a Remote Control and Monitoring System (RCMS) for NDB Hanjin KMW 250 RB, implementing science and technology as a form of collaboration between the education world and the aviation industry, Providing equipment maintenance data for maintenance management purposes. And in control directly in the technician's room to make it easier to monitor NDB Navigation Equipment. This design method is based on the Internet of Thing (IoT) The results of this design are able to provide a display of the parameters of the Air Navigation Equipment (NDB) in the Makassar Branch (MATSC),